Investigation of Mechanical and Melt Flow Properties of Polyamide 12 Composites of Different Reinforcement Materials - Mahmoud Abid; Zacharia Attia; Wael Elhrari; Abdalah Klash; Anour Shebani (African Journal of Advanced Pure and Applied Sciences, 2024)
The influence of inexpensive different fillers: marble powder, Libyan kaolin clay and white cement on the polyamide 12 (PA12) composite, to improve the mechanical properties and reduce the cost was investigated. Composites with (10, 20, 30, 40 and 50 wt% filler content) were produced using injection molding. The mechanical and melt flow properties were investigated. The results showed that the ultimate tensile strength, elongation at break, Young’s modulus, and Shore hardness of PA12 composites with 10 wt % marble and white cement were higher than that of pure PA12. In all PA12 composites, Young’s modulus and Shore hardness were higher than that of pure PA12 and increased with increasing the filler content. Although the impact strength values of PA12 composites decreased with increasing the filler content, the decrease in the impact strength values of PA12 composites with 10 wt % filler content was not significant compared to pure PA12. These results demonstrated that the addition of 10 and 20 wt % of marble and white cement to PA12 appear to improve certain properties such as ultimate tensile strength, elongation at break, Young’s modulus, and hardness with reasonable processability and no significant influence in the impact properties.